Blue box. Volume 8, A chance to blossom - Miura, Kouji (Manga author) (Shonen Jump manga., 2024)
"After the the actor playing the prince in the class play is knocked out of commission, Taiki is asked to take on the role. As nervous as he is, he follows through with the performance--until an accident befalls him and Hina! Can Taiki handle this shift in their already-precarious relationship?"--